2019
DOI: 10.1186/s13023-019-1218-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of impulsivity and inhibitory control deficits in the saccadic behavior of premanifest Huntington’s disease individuals

Abstract: Background: This study aims to test response inhibition in premanifest Huntington's disease individuals (Pre-HD), in the context of a saccadic paradigm with working memory demands and fronto-executive load as a way to measure inhibitory control deficits and impulsive behavior in Huntington's disease (HD). Methods: The oculomotor function of 15 Pre-HD and 22 Control individuals was assessed using an experimental paradigm comprising four horizontal saccadic tasks: prosaccade (PS), antisaccade (AS), 1-or 2-back m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…Biomarkers will play an important role in future therapeutic decisions now that C9orf72 mutation carriers can be identified by genetic testing many decades before symptoms begin [ 34 ], given that, with the emergence of antisense oligonucleotide therapies, the characterization of presymptomatic disease burden has now gained practical relevance [ 35 ]. Like in presymptomatic Huntington’s disease [ 36 ] and pre-ataxic Machado–Joseph disease [ 37 ] individuals, the recording of eye movements in presymptomatic C9orf72 gene carriers may have the potential as a biological marker. Thus, video-oculographic recording as an unbiased assessment of the neuropsychological condition might further prove its potential as a technical biomarker in the longitudinal work-up of the clinical condition from the presymptomatic to the symptomatic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers will play an important role in future therapeutic decisions now that C9orf72 mutation carriers can be identified by genetic testing many decades before symptoms begin [ 34 ], given that, with the emergence of antisense oligonucleotide therapies, the characterization of presymptomatic disease burden has now gained practical relevance [ 35 ]. Like in presymptomatic Huntington’s disease [ 36 ] and pre-ataxic Machado–Joseph disease [ 37 ] individuals, the recording of eye movements in presymptomatic C9orf72 gene carriers may have the potential as a biological marker. Thus, video-oculographic recording as an unbiased assessment of the neuropsychological condition might further prove its potential as a technical biomarker in the longitudinal work-up of the clinical condition from the presymptomatic to the symptomatic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HD is associated with deficits in decision making, which could explain the increased presence of dysfunctional behavior such as increased risk taking (Eddy & Rickards, 2012; Kalkhoven et al, 2014). Furthermore, impaired decision making, cognitive decline, obsessive behavior, and deficits in inhibitory control have been reported in HD mutation carriers without distinct motor symptoms (Beglinger et al, 2008; D'Aurizio et al, 2019; De Lucia, Peluso, Roca, De Michele, et al, 2019; Julio et al, 2019; Migliore et al, 2019; Paulsen & Long, 2014; Stout et al, 2011). Neuropsychological tasks assessing frontal executive functions such as the Symbol Digit Modalities Test, the Stroop Test, the Trail Making Test, and tasks requiring mental flexibility have been described to detected early impairment in HD mutation carriers (McGarry & Biglan, 2017; O'Rourke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous research has shown that temporal durations are judged as shorter when fewer attentional resources are engaged towards temporal information (Zakay, 1989). One could also speculate that this underestimation of time might be related to the impulsivity of HD patients, which has been documented with questionnaires (Johnson et al, 2017) or with inhibitory control tasks (Júlio et al, 2019), but we acknowledge that further research is needed to examine this issue more specifically.…”
Section: Discussionmentioning
confidence: 89%